Pembelajaran Sejarah Kebudayaan Islam di Madrasah Aliyah Swasta Al-Manar Medan Johor - Nasution, Abdul Gani Jamora; Putri, Devita Aulia; Hasanah, Nurul; Purba, Tiara Paramita BR; Putri, Winda Amelia; Jaffa, Zahra Azzura (AHKAM, 2022)
The history of Islamic culture is a very important lesson for us to learn to know the historical values and developments about Islam. Besides that, learning to ski is useful for forming the personality traits of the people to be even better than the exemplary journey of previous figures or generations. In general, the reality is that Islamic Cultural History lessons are less attractive to students. We conducted research at a private Madrasah Aliyah Al-Manar Medan Johor regarding the learning process, obstacle, obstacle solution to learn Islamic Cultural History. The method we use is a descriptive qualitative method. The objects we examined were students and teachers at the school. From the research results we obtained the implementation of SKI learnimg has been going well in accordance with the contents of lesson plan made by the SKI teacher and the obstacle that occur during the ski learning process namely students feel bored while studying, the class atmosphere is not conducive, students do not do their homework, students are sleepy in class, and students are lazy to study.Besides that, the teacher's efforts in these problems are by inviting refreshing by standing and shaking hands, inviting learning outside the classroom, giving directions to students to be quiet and listening to their reasons first if they don't do homework and advising not to repeat it, creating learning readiness, motivating students, creating harmony with students, provide guidance to students.